Sharing Tacit Knowledge in an Organizational Context - Different Profiles, Different Strategies - Oliveira, Márcio (2021)
Focusing the study's on sharing tacit knowledge in non-profit organizations (NPOs) in Portugal and taking as a case study the Portuguese volunteer firefighters (FBs), we listed as objectives ascertaining the profiles of Portuguese volunteer firefighters in the face of sharing tacit knowledge and identify action strategies to be implemented by these organizations, taking into account the different profiles of firefighters. A review of the literature on lessons learned and sharing of tacit knowledge allowed the identification of the main factors and typologies of barriers most prevalent in these organizations. A quantitative study carried out with 380 Portuguese firefighters made it possible to carry out a cluster analysis, which analysis of results made it possible to answer the established objectives. It was possible to identify the presence of 5 clusters distinct from each other, which include firefighters who favor different factors of sharing tacit knowledge and who identify different types of barriers to sharing tacit knowledge. Such scenario refers to different approaches, in the undertaking of efforts to promote the sharing of tacit knowledge, according to the profile of each cluster of firefighters. Studies in this area, aimed at the NPOs are scarce, as opposed to what happens in the private and public sectors. The case study option of organizations such as the Portuguese FBs, unique in their action and identity, accompanies the, increasingly recognized by society, need in enabling these organizations of competences for the best possible performance, in the face of tragic events that have occurred in recent years in Portugal.